Organic Food Consumption Behaviour: Sustainability, Symbol of Social Class, Luxury and Price - Hermin Istiasih (CV. AFDIFAL MAJU BERKAH, 2023)
This research tries to analyse the motives of consumers in Kediri, East Java, Indonesia in buying organic food. The four main motives that influence organic food consumption behaviour are sustainability, social class symbol, luxury and price investigated in this study. Questionnaires were used and given to 190 respondents. Data were analysed using Structural Equation Modelling and tested four hypotheses. The findings state that sustainability, social class symbols, and price significantly influence organic food consumption behaviour. There is no significant effect of luxury on organic food consumption behaviour. Based on these findings, strategies to improve quality, long-term health benefits, be environmentally friendly, and reduce the price of organic food should be implemented. This research draws on social practice theory as a critical lens for understanding organic food consumption not just as a result of individual choices, but as several interrelated 'relationships of action and speech'. This study investigates the consumption of organic food in East Java, Indonesia. Three consumption practices, which include investing in long-term welfare, expressing sustainability values, and signifying social status, so it can be concluded that organic food can be understood as a certain type of food as a trend food